The eastern Siberian tundra, a highly variable and uncertain greenhouse gas source - Hensgens, G.; Belelli Marchesini, L.; Vonk, J. E.; Dean, J. F.; Buzacott, A. J. V.; Petrov, R.; Karsanaev, S.; Maximov, T. V.; Dolman, H. J. (country:CA, 2024)
Following decades of warming at almost four times the average global rate (Rantanen et al. 2022), the Arctic is changing rapidly. The vast amounts of carbon stored in Arctic soils (Hugelius et al. 2014) present a potentially strong positive feedback loop. Siberia, home to a significant proportion of the global tundra, remains understudied and long-term greenhouse gas (GHG) monitoring using eddy covariance (EC) is scarce (Chu et al. 2017). With more than 15 years of data between 2003 and 2021, we present one of the longer EC monitoring series in eastern Siberia. We show that the eastern Siberian tundra is currently a highly variable and uncertain GHG source. Net CO2 uptake in the growing season is offset by methane emissions, roughly half of which are emitted outside of the carbon uptake season. The cumulative CO2 uptake has increased over the last decades. However, cumulative methane emissions are strongly coupled to carbon uptake, with roughly 1.97 g CO2eq-C emitted as methane per 1 g CO2-C taken up during the carbon uptake period. As a result, any future increase in tundra productivity is offset by enhanced methane release, strengthening the GHG source of the Siberian tundra.